Thermally reversible self-healing polysilsesquioxane structure-property relationships based on Diels-Alder chemistry - Jo, Young Yeol; Lee, Albert S.; Baek, Kyung-Youl; Lee, Heon; Hwang, Seung Sang (ELSEVIER SCI LTD, 2017)
An in-depth examination of the self-healing properties of both dienophile and diene functionalized ladder-like structured polysilsesquioxane copolymers and terpolymers was investigated. Through functionalization of both diene and dienophile on the double-stranded siloxane backbone with ternary n-alkyl functional groups acting as chain mobility control, the effect of chain mobility and chemical structure on self-healing and mechanical properties were elucidated. All of the single component self healing hybrid materials exhibited fast healing times (similar to 5 min), and their de-crosslinked adducts exhibited exceptional retention of solubility in common organic solvents for good reusability, all while having inherent high thermal stability and optical transparency. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: THERMOPLASTIC POLYSILSESQUIOXANES; SILSESQUIOXANES; POLYMERS; NANOCOMPOSITES; MEMBRANES; NETWORKS